Effect of high consumption the phyto-protein on quality of wound healingperineal on the postpartum at Primary Health Center Mlati II District Sleman - Sholaikhah Sulistyoningtyas; Yeni Komala (International Journal of Health Science and Technology, 2020)
Postpartum infections are still the leading cause of maternal death after bleeding and hypertension in pregnancy. The main cause of infection during the puerperal period is the presence of injury at perineum.Wound healing with perineal stitch quality assessment in the puerperium was expected to prevent postpartum mother from the danger of infection or physiological complaints that is by adding the intake or consumption of high protein diet in daily life.The purpose of this study was to determine the effect of high consumption of phyto-protein on perineal wound healing quality in postpartum mothers at Primary Health Center of Mlati II District Sleman Year 2017. The research design used was experimental research. The population used in this study was postpartum who maternally and experienced injury to the perineum. The result of p-value of REEDA scale shows p-value is 0,050=0,05 and for food record shows p value equal to 0,0000,05, then the test result is significant. Conclusion and Suggestion: There is effect that happen between  high consumption of phyto-protein to quality of perineum healing with p value  0,05 (p value 0,05). It is hoped that health workers can provide alternative counseling if they can not persuade postpartum women to abandon the culture of abstinence.